The Hyperlinked Society: Questioning Connections in the Digital Age - Tsui, Lokman (The New Media World, 2009)
"Links" are among the most basic---and most unexamined---features of online life. Bringing together a prominent array of thinkers from industry and the academy, The Hyperlinked Society addresses a provocative series of questions about the ways in which hyperlinks organize behavior online. How do media producers' considerations of links change the way they approach their work, and how do these considerations in turn affect the ways that audiences consume news and entertainment? What role do economic and political considerations play in information producers' creation of links? How do links shape the size and scope of the public sphere in the digital age? Are hyperlinks "bridging" mechanisms that encourage people to see beyond their personal beliefs to a broader and more diverse world? Or do they simply reinforce existing bonds by encouraging people to ignore social and political perspectives that conflict with their existing interests and beliefs? This pathbreaking collection of essays will be valuable to anyone interested in the now taken for granted connections that structure communication, commerce, and civic discourse in the world of digital media. "This collection provides a broad and deep examination of the social, political, and economic implications of the evolving, web-based media environment. The Hyperlinked Society will be a very useful contribution to the scholarly debate about the role of the internet in modern society, and especially about the interaction between the internet and other media systems in modern society." ---Charles Steinfield, Professor and Chairperson, Department of Telecommunication, Information Studies, and Media, Michigan State University Joseph Turow is Robert Lewis Shayon Professor at the Annenberg School for Communication, University of Pennsylvania. He was named a Distinguished Scholar by the National Communication Association and a Fellow of the International Communication Association in 2010. He has authored eight books, edited five, and written more than 100 articles on mass media industries. His books include Niche Envy: Marketing Discrimination in the Digital Age and Breaking up America: Advertisers and the New Media World. Lokman Tsui is a doctoral candidate at the Annenberg School for Communication, University of Pennsylvania. His research interests center on new media and global communication. Cover image: This graph from Lada Adamic's chapter depicts the link structure of political blogs in the United States. The shapes reflect the blogs, and the colors of the shapes reflect political orientation---red for conservative blogs, blue for liberal ones. The size of each blog reflects the number of blogs that link to it. digitalculturebooks is an imprint of the University of Michigan Press and the Scholarly Publishing Office of the University of Michigan Library dedicated to publishing innovative and accessible work exploring new media and their impact on society, culture, and scholarly communication. Visit the website at www.digitalculture.org.